Environmental humanities and climate change: understanding humans geologically and other life forms ethically. (24th October 2017) - Robin, Libby
Abstract : Luminous Relic 2017: Alexander Boynes, Mandy Martin, and Tristen Parr; pigment, sand, crusher dust, acrylic on linen; three‐channel high‐definition video; stereo sound score; 6′10″ duration; 260 cm × 1170 cm. Courtesy of the artists and Australian Galleries, Melbourne and Sydney. (Geelong Gallery install). Photographer: Andrew Curtis. Shown as part of the CLIMARTE festival 2017, Luminous Relic 2017 is an example of the multimedia performance art that complements the environmental humanities. Abstract : The task of reconceptualizing planetary change for the human imagination calls on a wide range of disciplinary wisdom. Environmental studies were guided by the natural sciences in the 1960s, and in the 1970s broadened to include policy and the social sciences. By the 1990s, with global environmental changes well‐documented, various humanist initiatives emerged, expanding the idea of ethics, responsibility and justice within the transdisciplinary mode of environmental studies. Shared problems, places, and scales form the basis for collaborative work in the environmental humanities, sometimes in partnerships with natural sciences and the creative arts. Experiential learning and trust in judgments based on different methods typically guide humanities interventions. Shifting the frameworks of environmental research to be more consciously inclusive and diverse is enabling concepts of the physical world that better include humans and taking ethics beyond humans to consider more‐than‐human Others. This review considers historically how the environment and the humanities became conceptualized together. It then explores three emerging fields in transdisciplinary environmental scholarship where environmental humanities are playing major leadership roles: (1) climate and biodiversity justice, both for humans and for other forms of life; (2) the Anthropocene as a metaphor for living with planetary changes and (3) life after 'the end of nature, ' including rewilding and restoration. While environmental humanities also work in many other fields, these cases exemplify the crucial tasks of situating the human in geological and ecological terms and other life forms (the 'more‐than‐human') in ethical terms. WIREs Clim Change 2018, 9:e499. doi: 10.1002/wcc.499 This article is categorized under: Climate, History, Society, Culture > Disciplinary Perspectives